Correlation, age and significance of Turonian Chalk hardgrounds in southern England and northern France: The roles of tectonics, eustasy, erosion and condensation. (November 2019) - Gale, Andy
Abstract: The stratigraphy and correlation of middle and upper Turonian hardgrounds developed around the margins of the Anglo-Paris Basin in southern England (Chalk Rock) and Normandy (Tilleul Hardgrounds) are reassessed using microcrinoid stratigraphy. The Chalk Rock was formed by two, discrete events – an earlier, erosional or non-depositional hiatus that cuts out much of the middle Turonian in Dorset and Wiltshire (Ogbourne Hardground) and extends across the English Channel to Normandy as the Tilleul Hardgrounds, and a later, strongly condensed succession of late Turonian age, developed from the Chilterns westwards across to Wiltshire (Fognam Farm, Blount's Farm, Hitch Wood Hardgrounds). Where the two events intersect, in Wiltshire, the Lewes Chalk is very thin. The lower event is of lower Romaniceras ornatissimum Zone age, and is a local representation of a short-lived, globally identifiable eustatic low. The condensation associated with the upper part of the Chalk Rock can be attributed to relative non-subsidence across a region of relatively shallow basement in the western part of its development. No evidence has been found of tectonic inversion in the Turonian along the Purbeck-Isle of Wight structure, but very local, penecontemporaneous movement on the Litton Cheney Fault in Dorset generated a conglomerate of older Cretaceous (Albian, Cenomanian, Turonian) rocks redeposited within the middle Turonian. The base of the Lewes Chalk Formation is strongly diachronous across southern England, younging from west to east. The formation of the Chalk Rock and equivalent deposits in France can be related to an eustatic low during middle and late Turonian times. The development of individual Chalk Rock hardgrounds is possibly caused by minor eustatic lows, driven by the long eccentricity cycle (405 kyr).